Trashboom Ponton Adaptif sebagai Solusi Mitigasi Sampah pada Intake Glapan Barat, Daerah Irigasi Glapan, Kabupaten Grobogan - Retno Sri Waryani; Ian Karunia Perkasa (Journal of Innovative and Creativity, 2026)
Floating debris accumulation at irrigation intakes often obstructs flow discharge and increases the risk of sluice gate damage, particularly in rivers with high water level fluctuations such as the Tuntang River. This study aims to design an adaptive Trashboom to mitigate debris accumulation at the West Glapan Intake. The method employed is applied engineering design utilizing 8-inch PVC pipes as pontoons and galvanized hollow iron as the main frame. The design results demonstrate that this pontoon Trashboom structure is capable of vertically adapting to flood water elevations and effectively diverting debris to the riverbank through a self-clearing mechanism caused by its diagonal placement. This solution offers construction cost efficiency and ease of maintenance compared to mechanical trashracks, while ensuring the continuity of irrigation water supply.